A comparative study showing the impact of incentives on job satisfaction among employees at Zefta Specialized Hospital, Egypt, and Jalu Central Hospital, Libya. - Enwegi, Ali Ibrahim; الراعي هالة عبد العزيز; مازن ليلي; مطر حمدي عبد الباقي (Tobruk University Journal of Social and Human Sciences, 2025)
Countries tend to increase production and raise the efficiency of the worker, and that one of the factors for increasing production is job satisfaction, and to reach this goal, there must be material and moral incentives, and the development of management to reach that goal, so this was a comparative study that shows the effect of incentives on job satisfaction among workers in Zefta Specialist Hospital/ Egypt and Gallo Central Hospital / Libya, where a comparison study was made between them in terms of gender, age, educational qualification, job experience, and the administrative level of the job, and a questionnaire consisting of 38 questions was made on the Likert system and the SPSS program version 2023 was used to obtain statistical results and analyze them at the level of significance α = 0.05 and testing the validity of the questionnaire to study the relationship between motivation and job satisfaction as well as accepting. The results concluded: - There is a statistically significant relationship between incentives and job satisfaction. - There is a statistically significant relationship between incentives and training. - There is no statistically significant relationship between incentives and decision making. - There is a statistically significant relationship between incentives and risk tolerance. There is a statistically significant relationship between incentives and job affiliation. - There is a statistically significant relationship between incentives and communication. There is a statistically significant relationship between incentives and powers. - There is a statistically significant relationship between incentives and creative ideas.